Service function chain construct algorithm based on reliability - Julong LAN; Zijin JIN; Penghao SUN; Yiming JIANG; Yue WANG (Tongxin xuebao)
With the continuous expansion of network size and content quantity,network operators often face the problem of data transmission interruption,thus how to improve the reliability of data transmission has become a research hotspot.Started with the huge advantages of NFV environment over traditional TCP/IP architecture based on the background that every network node has the capability of security service,a reliability algorithm for constructing functional service chains was proposed.First,the network topology was introduced and abstracted it into a digraph for a better analyzation.Then,several quantitative indices were used to define the upper and lower bounds of failure probability and resolved the model through a heuristic algorithm.The experimental results show that the proposed algorithm increases the reliability of service chain selection and spends less time.